New evidence of ethanol's anxiolytic properties in the infant rat - Miranda Morales, Roberto Sebastián (2014)
Ethanol induces appetitive, aversive, and anxiolytic effects that are involved in the development ofethanol use and dependence. Because early ethanol exposure produces later increased responsiveness toethanol, considerable effort has been devoted to analysis of ethanol’s appetitive and aversive propertiesduring early ontogeny. Yet, there is a relative scarcity of research related to the anxiolytic effects ofethanol during early infancy, perhaps explained by a lack of age-appropriate tests. The main aim of thisstudy was to validate a model for the assessment of ethanol’s anxiolytic effects in the infant rat (postnataldays 13e16). The potentially anxiolytic effects of ethanol tested included: i) amelioration of conditionedplace aversion, ii) ethanol intake in the presence of an aversive conditioned stimulus, iii) the inhibitorybehavioral effect in an anxiogenic environment, and iv) innate aversion to a brightly illuminated area in amodified light/dark paradigm. Ethanol doses employed across experiments were 0.0, 0.5, and 2.0 g/kg.Results indicated that a low ethanol dose (0.5 g/kg) was effective in attenuating expression of a condi-tioned aversion. Ethanol intake, however, was unaffected by simultaneous exposure to an aversivestimulus. An anxiogenic environment diminished ethanol-induced locomotor stimulation. Finally, ani-mals given 0.5 g/kg ethanol and evaluated in a light/dark box showed increased time spent in the illu-minated area and increased latency to escape from the brightly lit compartment than rats treated with ahigher dose of ethanol or vehicle. These new results suggest that ethanol doses as low as 0.5 g/kg areeffective in ameliorating an aversive and/or anxiogenic state in preweanling rats. These behavioralpreparations can be used to assess ethanol’s anxiolytic properties during early development.